Comparison of expression of molecular markers of peripheral blood lymphocyte activation in patients with small uveal melanoma and healthy controls (Ukrainian Journal of Ophthalmology, 2026)
Background: Organ-saving treatment is indicated for patients with small (i.e., ? 3 mm in prominence) uveal melanomas (UM), that being the initial stage of the disease. Association between the level of activation of the immune system and the progress of UM has been demonstrated in recent decades. Investigation of the expression of molecular markers of lymphocyte activation is important and required for predicting tumor responses to various treatments and choosing the most effective treatment for the disease.Purpose: To investigate the expression of molecular markers of peripheral blood lymphocyte activation in patients with small uveal melanomas prior to treatment.Methods: We compared the expression of molecular markers of peripheral blood lymphocyte activation in 16 patients with small uveal melanoma (prior to treatment) and 44 healthy controls (donors).Results: Prior to treatment, patients with small uveal melanoma were found to have elevated expression of molecular markers of peripheral blood lymphocyte activation compared to healthy controls (р < 0.0002).Conclusion: In uveal melanoma patients at the initial stage of the disease (i.e., with tumors ? 3 mm in prominence), the functional activity of immune competent cells of the body in response to tumor development was found to involve the following: (a) activation of lymphocyte IL-2 receptors (CD25+), (b) increased indices of lymphocyte activation and proliferation (CD38+, CD45+, CD150+),  immunoglobulin production (CD150+), and intercellular adhesion (CD54+) and apoptosis (CD 95+), and (c) induction of cytokine secretion (CD7+).
Keywords: small uveal melanoma; molecular markers of peripheral blood lymphocyte activation